Usability evaluation of a small church website - Lea, Daniel D. (University of Wisconsin--Stout, 2019)
This study examines the special characteristics technical and professional communicators must consider when designing and evaluating church and nonprofit websites. This study included a literature review, which found that these categories of organizations have been slower to fully embrace web technology than their commercial counterparts. This has been the result of multiple factors, including lack of technical ability and concerns about the implications of trying to recreate or enhance an in-person experience in the digital realm. The study also found that there are special considerations involved for such websites, including the rhetorical situation, level of independence of the organization, and goals of creating an online presence. These findings were applied to a usability analysis of a small church website representing two affiliated United Methodist churches. The usability study employed a heuristic evaluation, cognitive walkthrough, and user test including 10 participants representing non-members and members of the churches. This study makes an original contribution in that it combines research into the content, usability, and rhetorical considerations that are unique to church and nonprofit websites and demonstrates the application of the concepts in the context of the evaluation of a local church website.
Keywords: Web sites; Digital communications; United Methodist Church (U.S.)